Improving 3D perception by adding eye-tracking based motion parallax - an ICASSP demo - Florencio, Dinei; Zhang, Cha (ICASSP, 2009)
Motion parallax is one of the most important 3D clues for human vision perception. The majority of the monitors today display contents regardless of the user’s viewpoint. In this demo, we track head/eye position of the viewer based on a web camera, and use that information to render view-dependent contents, adding motion parallax to essentially any display device. In the demo we will allow ICASSP participants to try out the system, and perceive the sensation of depth provided by the technology, which is much cheaper and complementary to stereoscopic displays.